1994
DOI: 10.1111/j.1365-2605.1994.tb01260.x
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro promoting role for hydrogen peroxide in human sperm capacitation

Abstract: A complex process of maturation called capacitation is an essential step for spermatozoa to fertilize oocytes. Recent studies have shown that reactive oxygen species (ROS) can enhance the capacitation of human spermatozoa and sperm-zona interaction. We have investigated whether hydrogen peroxide (H2O2) could trigger capacitation of human spermatozoa and the acrosome reaction. The addition of catalase, a specific H2O2 scavenger, at the beginning of the capacitation process decreased the levels of both hyperacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
65
0
4

Year Published

1995
1995
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(78 citation statements)
references
References 40 publications
7
65
0
4
Order By: Relevance
“…9). As the latter specifically scavenges hydrogen peroxide, these data support the notion that this oxidant is a physiological mediator of sperm function, driving both the tyrosine phosphorylation events associated with sperm capacitation (Bize et al 1991, Griveau et al 1994, Rivlin et al 2004, O'Flaherty et al 2006a and facilitating the acrosome reaction (Hsu et al 1999, O'Flaherty et al 2005. It is interesting to note that overall, phenylalanine is a much more powerful stimulus for the acrosome reaction than progesterone.…”
Section: Discussionsupporting
confidence: 64%
“…9). As the latter specifically scavenges hydrogen peroxide, these data support the notion that this oxidant is a physiological mediator of sperm function, driving both the tyrosine phosphorylation events associated with sperm capacitation (Bize et al 1991, Griveau et al 1994, Rivlin et al 2004, O'Flaherty et al 2006a and facilitating the acrosome reaction (Hsu et al 1999, O'Flaherty et al 2005. It is interesting to note that overall, phenylalanine is a much more powerful stimulus for the acrosome reaction than progesterone.…”
Section: Discussionsupporting
confidence: 64%
“…Particular attention has been given to the harmful effects of ROS on in vitro spermatozoa and the implications of this in semen preparation in In Vitro Fertilization (IVF) programs. However, some reports have shown that ROS can trigger in vitro physiological sperm functions, such as capacitation and hyperactivated motility (103)(104)(105). These positive effects are strictly related to the equilibrium between ROS and the scavenger systems.…”
Section: Seminal Fluid and Ros Damagementioning
confidence: 99%
“…Different oxygen radicals such as superoxide anion, nitric oxide, and hydrogen peroxide have been related to sperm capacitation (Griveau et al 1994, de Lamirande et al 2009) and the addition of ROS yields an increase in PY in a variety of species (Baumber et al 2003, Roy & Atreja 2008, Kota et al 2010, Dona et al 2011. It has recently been shown that ROS generation during capacitation may be necessary for cholesterol efflux from the sperm plasma membrane.…”
Section: Introductionmentioning
confidence: 99%